THE RELEVANCE OF IBN TAYMIYYAH ECONOMICS IN ADDRESSING POVERTY AND INCOME DISTRIBUTION - Adetio Setiawan, Romi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2016)
The Relevance of Ibn Taymiyyah Economics in Addressing Poverty and Income Distributio n. This paperexamines the view of Ibn Taymiyyah of state or government in Islamic law and the state role in the distribution of wealth and removing the class differences and income injustice within an economic order, and analyze the various problems in most of modern government to tackle poverty and income distribution? And how to remove class differences and income injustice within an economic order? According to Ibn Taymiyyah, the government is responsible for regulating the distribution of income of the rich people to the poor people equitably, and balancing the level of life of the people. Ibn Taymiyyah above statement can be realized on the government’s authority to levy taxes on the rich and tax revenue is distributed to the development of infrastructure and other expenses that will improve human development and create employment. The idea is relevant to reduce unemployment and poverty in today Muslim countries